PENERAPAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) TERHADAP MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK PADA MATERI DUNIA HEWAN KELAS X DI SMA UNGGUL NEGERI 8 PALEMBANG - Msy Hikmah; Yenny Anwar; Riyanto Hamid (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2018)
This research aims to know the effects of the implementation of Team Games Tournament (TGT) learning method on motivation and learning achievement of kingdom animalia topic in class X of SMA Unggul Negeri 8 Palembang. This research uses Quasi Eksperimental research methodology with Non-equivalent Control Group Design. The test data collection of learning motivation and learning achievement skill is done on X IPA 4 as the experimental class and X IPA 6 as the control class. The sample collection technique is random sampling. The acquired t value analysis of motivation data using SPSS of 9,590 > t tabel of 2,000. The acquired t value analysis of learning achievement data using SPSS of 9,634 > t tabel of 2,000. The average score of motivation of experimental class is 80,39, while the control class is 67,24. The average value of students learning achievement in the experimental group was higher than the control group. This was proven by the average value of the test learning achievement  acquired in the experimental group amounted to 80,44, while the control group was 60,42, so HO is rejected, which means that there were significat implementation of Team Games Tournament (TGT) learning method on motivation and learning achievement of kingdom animalia topic in class X of SMA Unggul Negeri 8 Palembang. Keywords : Team Games Tournament (TGT) Model, Motivation, Learning Achievement, Kingdom Animalia.